Stability analysis in generalist predator-prey dynamics with predator harvesting - S. Vijaya; S. Ganga (Computational Ecology and Software)
This paper seeks to explore the stability assessment of a generalist predator-prey system with predator harvesting. The study presents a model examining the dynamics between primary prey and predator, considering the existence of a generalist predator. Prey growth follows a logistic rate, while predator consumption is modeled with a cyrtoid functional response. In the absence of primary prey, the predator population adopts a generalist strategy, akin to the Beverton-Holt model. The model also incorporates harvesting on the predator population. We analyze the model's equilibrium, stability, positivity, and boundedness, and use numerical simulations to explore its predictions. This study enhances our understanding of ecological interactions and supports the development of effective conservation and management strategies.